The Role of Subsidized Fertilizers on Rice Production and Income of Farmers in Various Land Typologies - Wildayana, Elisa; Armanto, M Edi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2019)
The research aimed to analyze the role of subsidized fertilizers on rice production and income of farmers in various land typologies. The sampling used is cluster method and followed with an experimental research by using Split Plot Design. The compound fertilizer costs are one-half times higher than single fertilizer, but the rice yield difference is enhanced by the provision of fertilizer reaching more than two-times higher compared to a single fertilizer. The rice yields can be increased more than three-times higher, but the income of farmers can be increased only about one and half times. The Government needs to make a policy of the lowest rice price, then income of farmers can be automatically increased and at the same time the welfare of famer’s families will be also increased.